Combined large cell neuroendocrine carcinoma and squamous cell carcinoma of the oropharynx: A collision course of tumors. Issue 1 (27th January 2022) - Rossi, Nicholas A.; Gietzen, Rachelle; Malaya, Lauren T.; Haroun, Kareem B.; Conner, Grant R.; Coblens, Orly; Resto, Vicente A.; Clement, Cecilia G.; Joshi, Rohan
Abstract: Combined large cell neuroendocrine carcinoma (LCNEC) and squamous cell carcinoma (SCC) of the H&N are exceptionally rare. We present the case of combined p16 negative SCC and LCNEC of the oropharynx treated with combination chemotherapy. This is the third reported case of combined neuroendocrine carcinoma and SCC of the oropharynx. Abstract : Large cell neuroendocrine carcinoma (LCNEC) of the H&N is an exceptionally rare entity that has occasionally been reported to occur as a component of combined or "collision" tumors. Here, we cite a rare case of combined H&N LCNEC and squamous cancer.